Tube-wall catalytic membrane reactor for hydrogen production by low-temperature ammonia decomposition. (3rd June 2021) - Itoh, Naotsugu; Kikuchi, Yosuke; Furusawa, Takeshi; Sato, Takafumi
Abstract: Ammonia has attracted great interest as a chemical hydrogen carrier. However, ammonia decomposition is limited kinetically rather than thermodynamically below 400 °C. We developed a tube-wall catalytic membrane reactor that could decompose ammonia with high conversion even at temperatures below 400 °C. The reactor had excellent heat transfer characteristics, and thus nearly 100% conversion for an NH3 feed of 10 mL/min at 375 °C was achieved with a 2-μm-thick palladium composite membrane, and hydrogen removal from the decomposition side resulted in a large kinetic acceleration. Graphical abstract: Image 1 Highlights: Ammonia decomposition is limited kinetically rather than thermodynamically below 400 °C. A new type reactor, i.e., tube-wall catalytic membrane reactor (TWMR) was proposed. The TWMR consists of a tube-wall catalyst and a palladium membrane tube. Nearly 100% conversion at 375 °C was obtained by using a 2 μm thick palladium membrane.